ELAN 2019 Highlights - English Language Arts Network (ELAN) (2019)

Response to CAM Report on Systemic Racism in the Arts - English Language Arts Network (ELAN) (2019)

Statement Regarding Member Resignations from QCGN - Council for Anglophone Magdalen Islanders (CAMI); Committee for Anglophone Social Action (CASA); English Community Organization of Lanaudière (ECOL); English Language Arts Network (ELAN); Megantic English-speaking Community Development Corporation (MCDC); Neighbours Regional Association of Rouyn-Noranda; North Shore Community Association (NSCA); Quebec Writers' Federation (QWF); Vision Gaspé-Percé Now (VGPN); Voice of English-speaking Quebec (VEQ); 4 Korners Family Resource Center (2019)

Bright Beginnings Project Descriptions - Community Health and Social Services Network (CHSSN) (2019)

15 Years of ELAN - English Language Arts Network (ELAN) (2019)

Bill 21 Discriminates Against Quebecers : Statement from ELAN - English Language Arts Network (ELAN) (2019)
Keywords: Official Language Minority Community (OLMC)

ELAN (English-Language Arts Network) est heureux d’annoncer le lancement du programme de subventions Artistes Inspire (AI), soit un investissement de 2,2 millions de dollars destiné à créer des activités artistiques et culturelles dans les écoles de langue officielle en situation minoritaire au Québec - English Language Arts Network (ELAN) (2019)
Keywords: Official Language Minority Community (OLMC)

ELAN launches ArtistsInspire Grants (AIG), a $2.2 Million Investment for Quebec Official-language Minority Schools to Create Arts and Cultural Opportunities - English Language Arts Network (ELAN) (2019)
Keywords: Official Language Minority Community (OLMC)

ELAN Inclusion Plan - English Language Arts Network (ELAN) (2019)
In summer 2017, after several years of internal discussion, the English Language Arts Network (ELAN) embarked on a process of creating an inclusion plan. This plan addresses our overall direction as an organization, as well as our work in the specific areas of membership, human resources, governance, advocacy, and communications. At the heart of this plan is an acknowledgement that our work on inclusion and diversity is ongoing, will evolve, and will involve mistakes. It is active work, involving all of us and all parts of ELAN. When ELAN began in 2004, the organization was focused on building positive bridges between the French- and English-speaking arts communities. This focus will remain present throughout our work. However, we recognize that in the fifteen years since ELAN started, the context of the arts community has shifted and other issues have been raised.

State of the Arts...Activation Conference Official Program - English Language Arts Network (ELAN) (2019)

Annual $1500 Grants for English Public Elementary & Secondary Schools 2019-2023 : ArtistsInspire Grants Online and In-Person Art Workshops - English Language Arts Network (ELAN) (2019)
Support for Schools and Artists from Quebec's English-speaking communities to connect through hands-on creative experiences an ELAN/LEARN partnership funded by the Government of Canada's Action Plan for Official Languages

Annual Funding from 2019-2023 : Artists Inspire Grants - English Language Arts Network (ELAN) (2019)
Support for Schools and Artists from Quebec's English-speaking communities to connect through hands-on creative experiences an ELAN/LEARN partnership funded by the Government of Canada's Action Plan for Official Languages

ELAN 15 Year Anniversary Booklet - English Language Arts Network (ELAN) (2019)

Research Project : Prototype Digital Solutions (ARTS2U) Final Report - English Language Arts Network (ELAN) (English-Language Arts Network (ELAN), 2019)
Between August 2018 and March 2019, ELAN's Prototype Digital Solutions research project conducted prototype development toward a more effective digital marketing system for Quebec-based English-language arts producers. For the purpose of communications and marketing, and as a unifying title for the prototype and the research components, the project uses the working title of ARTS2U .
Keywords: Official Language Minority Community (OLMC)

Annual Report 2018-2019 - Leading English Education and Resource Network (LEARN) (2019)

Youth Internships in Community Media : A First Step Towards Capacity Building for Official Language Community Media in Minority Setting - Consortium of Official Language Minority Community Media (2018)
Keywords: Official Language Minority Community (OLMC)

ELAN Quebec Thrilled with Government of Canada’s $7.5 Million Investment in Arts and Culture Micro-grants for Official Language Minority Schools - English Language Arts Network (ELAN) (2018)
Keywords: Official Language Minority Community (OLMC)

ELAN's 14th Annual General Meeting - English Language Arts Network (ELAN) (2018)
Keywords: Official Language Minority Community (OLMC)

ELAN presents Arts Alive! Québec : Successful Multi-region Arts Festival Returns for 4th Exciting Year - English Language Arts Network (ELAN) (2018)

Digital Solutions to Connect Artistic Producers with Cultural Consumers - English Language Arts Network (ELAN) (English-Language Arts Network (ELAN), 2018)
Between January and March 2018, ELAN's Digital Solutions research project surveyed artists, arts organizations, publicists, journalists, media specialists and technical specialists, and hosted two focus group sessions.

Re: Broadcasting Notice of Consultation CRTC 2017-183, Renewal of Société de télédiffusion du Québec licence, 2017-0830-7 - English Language Arts Network (ELAN); Rodgers, Guy (2018)
Keywords: Official Language Minority Community (OLMC)

Request for Proposals: Communications Specialist to Develop Outreach Plans & Tools to Promote Micro Grants Program for Arts & Culture in English Schools in Quebec - English Language Arts Network (ELAN) (2018)

In Quebec & Tour Ready : A Booklet of 41 Quebecois Performing Artists and Their Tour Ready Work - English Language Arts Network (ELAN) (2018)

Job Posting : Events & Access Coordinator - State of the Arts III - English Language Arts Network (ELAN) (2018)

Job Posting : Project Manager - State of the Arts III - English Language Arts Network (ELAN) (2018)

Annual Report 2017-2018 : Leading the Way - Leading English Education and Resource Network (LEARN) (2018)

Grant Writing Principles - Park, June (2018)

Response to ELAN Member and Community Questions for Simon Brault - English Language Arts Network (ELAN); Canada Council for the Arts (2017)

13th Annual AGM Motions for Discussion - English Language Arts Network (ELAN) (2017)

Culture in the Schools - Application Guide - English Language Arts Network (ELAN) (2017)

Proposed Fee Structure: Pay What You Can (PWYC) - English Language Arts Network (ELAN) (2017)

Annual Report 2016-2017 - Leading English Education and Resource Network (LEARN) (2017)

Public Consultation on Canadian Content in a Digital World - English Language Arts Network (ELAN); Forget, Bettina; Rodgers, Guy (2016)
Keywords: Official Language Minority Community (OLMC)

Coneil des arts et des lettres du Québec (CALQ) : Information Session - Individual Artist Programs - Rozencwajg, Laurent (2016)
More than 80 artists representing a diversity of artistic disciples were present. Their questions enriched the presentation and are incorporated in the summary.

Conseil des arts et des lettres du Québec - Rozencwajg, Laurent (2016)

Short History of Official Language Advocacy : English-Language Television in Quebec - English Language Arts Network (ELAN) (2016)
Keywords: Official Language Minority Community (OLMC)

AGM Package : ELAN's 12th Annual General Meeting - English Language Arts Network (ELAN) (2016)
Keywords: Official Language Minority Community (OLMC)

ELAN's ACE Initiative TEST! Projects Applicant Guide - Armeni, Virginia; Huff, Christie; Knowles, Paula; English Language Arts Network (ELAN) (2016)

ACCORD Artists Tool Kit - English Language Arts Network (ELAN) (2016)
ACCORD was a 2-year pilot project (2011- 2013). Artists are always seeking new audiences. Communities and schools around Quebec appreciate performances and presentations by live artists. ACCORD connected artists and communities in new and diverse ways. The launch of the ACCORD website marked the beginning of the active part of the ACCORD Project. In Year 2, ACCORD worked with regional partners to kickstart pilot events in communities around the province, while continuing efforts to develop the online Tool Kit and to recruit new artists and presenters to join the network.

ACCORD Educators Tool Kit - English Language Arts Network (ELAN) (2016)
ACCORD was a 2-year pilot project (2011- 2013). Artists are always seeking new audiences. Communities and schools around Quebec appreciate performances and presentations by live artists. ACCORD connected artists and communities in new and diverse ways. The launch of the ACCORD website marked the beginning of the active part of the ACCORD Project. In Year 2, ACCORD worked with regional partners to kickstart pilot events in communities around the province, while continuing efforts to develop the online Tool Kit and to recruit new artists and presenters to join the network.

ACCORD Presenters Tool Kit - English Language Arts Network (ELAN) (2016)
ACCORD was a 2-year pilot project (2011- 2013). Artists are always seeking new audiences. Communities and schools around Quebec appreciate performances and presentations by live artists. ACCORD connected artists and communities in new and diverse ways. The launch of the ACCORD website marked the beginning of the active part of the ACCORD Project. In Year 2, ACCORD worked with regional partners to kickstart pilot events in communities around the province, while continuing efforts to develop the online Tool Kit and to recruit new artists and presenters to join the network.

Arts, Education, and Health Service Providers for Youth : As Published for Yeah! Quebec, August 2016 - English Language Arts Network (ELAN) (2016)

Year-End Report - Leading English Education and Resource Network (LEARN) (2016)
The Leading English Education and Resource Network (LEARN) is a non-profit organization that serves the public, private, anglophone and aboriginal Youth and Adult Education sectors of Québec. We bring together the expertise and efforts of educators, students, parents and partners in our community to cultivate success for all learners.

ELAN Presents Arts Alive! Québec - English Language Arts Network (ELAN) (2016)

Cultural Tourism and Touring Research - Nasrallah, Dimitri (2016)

Cultural Tourism and Touring Research : Funded by Innovation, Science and Economic Development Canada - Nasrallah, Dimitri; English-Language Arts Network (ELAN) (English-Language Arts Network (ELAN), 2016)
ELAN Quebec’s core objectives over the next four years are to cultivate and expand upon communication, research, and market-access networks that the organization has already initiated in the English-speaking communities of Quebec (ESCQ). ELAN will execute its network-development strategy through the pursuit of numerous concurrent activities that involve existing and future partnerships with different stakeholders. Activities have been devised across two broad phases: Phase 1 focuses on cultivating and strengthening various networks within Quebec. Phase 2 focuses on expanding the various networks cultivated in Phase 1 beyond Quebec’s borders, to find new audiences for ESCQ culture in Ontario, the Maritimes, and the northeastern United States.
Keywords: Official Language Minority Community (OLMC)

Visual Market Access: Panel Discussion with NYC Gallerists - English Language Arts Network (ELAN) (2016)

A Market Access Strategy for Official Language Minority Artists in Quebec - English Language Arts Network (ELAN) (2016)
In 2013, the Canada Council launched an initiative to facilitate market access in which they wished to include a minority-language component as part of the Road Map for Official Languages 2013-2018. The Council funded ELAN to elaborate a Market Access Strategy for Performing Arts on behalf of the English-speaking community of Quebec. This work began in May 2015. The solutions recommended by the Market Access Strategy could be submitted to the Council for funding during the life of the current initiative (2013-2018).
Keywords: Official Language Minority Community (OLMC)

YEAH! Successful Projects - English Language Arts Network (ELAN) (2016)

Re: CRTC 2015-421-4 : A Review of the Policy Framework for Local and Community Television Programming - Rodgers, Guy (2016)

Brief for Official Language Policy Review 2016 - English Language Arts Network (ELAN) (2016)
ELAN was conceived in November 2004 at the Quebec Arts Summit held in Montreal. More than 120 artists and other representatives of the English-speaking arts milieu, as well as government officials, came together to discuss ways to support artists and cultural workers in Quebec’s official language minority community (OLMC). With the support of sister organizations the Quebec Drama Federation (QDF), the Quebec Writers’ Federation (QWF), and the Association of English-Language Publishers of Quebec (AELAQ), ELAN was created to give a united voice to minority English-language artists of all backgrounds, working in all disciplines, and living in all regions of Quebec. Through networking events, a monthly email newsletter (ELANews), needs assessment surveys, and major projects such as the Arts Alive! Québec community festivals, ELAN has worked to bring Quebec artists closer together and spread their work far and wide.
Keywords: Official Language Minority Community (OLMC)

Re: A Review of the Policy Framework for Local and Community Television Programming : CRTC 2015-421 - Rodgers, Guy (2015)

ELAN to be Represented on Matv Advisory Committee - English Language Arts Network (ELAN) (2015)

Culture, Creativity, Confluence and Collision - Rodgers, Guy (2015)

Guy Rodgers Named Compagnon (Champion) of the Ordre des arts et des lettres du Québec - English Language Arts Network (ELAN) (2015)

Visiting Gallerists from New York and Boston : Panel Discussion at OBORO - 4001 Berri, local 301 - English Language Arts Network (ELAN) (2015)

ELAN Board of Directors Update : Peter MacGibbon Moves on, Bettina Forget Welcomed as Interim President - English Language Arts Network (ELAN) (2015)

Building a Career as an Artist - Macdonald, Amy; Shaughnessy, Kyra (2015)

Activity Report 2014-15 - English Language Arts Network (ELAN) (2015)

Grantwriting Principles - Park, June; Majewski, Monika (2015)
Keywords: Official Language Minority Community (OLMC)

Grantwriting Workshops - Fall 2015 Participant Resource Package - Park, June; Majewski, Monika (2015)

Quebec and Us : A Mutation of Identity - Rodgers, Guy (Diversité Artistique Montréal (DAM), 2015)

Digital Shift Project Final Report - Burnett, Richard (English-Language Arts Network (ELAN), 2014)
Between April and October 2014, ELAN's Digital Shift project surveyed artists, arts organizations, publicists and journalists, and then hosted two focus group sessions, to create a report with recommendations to help artists, arts organizations and their audiences adapt to the digital shift from old media to new media.

Celebrate the English Language Arts Network's 10th Anniversary : ELAN Marks Tenth Year of Creating Stronger Networks for Quebec's English-speaking Artists - English Language Arts Network (ELAN) (2014)

Re: 2013-1746-2 : Non-compliance Complaint Regarding MATV by Sabine Friesinger (OBCI) - Rodgers, Guy (2014)

Crowdfunding and the Arts : A Panel Discussion Co-hosted by ELAN and Studio XX - English Language Arts Network (ELAN) (2014)

Update on Community TV - English Language Arts Network (ELAN) (2014)

Digital Shift Survey-Artists and Arts Organizations - English Language Arts Network (ELAN) (2014)

Digital Shift Survey : Media - English Language Arts Network (ELAN) (2014)

Digital Shift Survey : Publicists - English Language Arts Network (ELAN) (2014)

ELAN's Guy Rodgers Elected for Another Term on Culture Montréal Board - English Language Arts Network (ELAN) (2013)

Brief Submitted to the National Assembly of Quebec’s Committee on Culture and Education by the English Language Arts Network for the General Consultation and Public Hearings on Bill 14 : An Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and Other Legislative Provisions - English Language Arts Network (ELAN) (2013)
This brief was prepared by the English-Language Arts Network (ELAN), an incorporated not-for-profit organisation that represents 8,000 English-speaking artists in Quebec. ELAN is a meeting place for English-language artists and cultural workers of all disciplines from every region of Quebec, where they can share expertise and resources, build audiences and alliances, seek support, advocate for their interests, and make common cause with the Francophone arts community.

The Sheila & Victor Goldbloom Distinguished Community Service Award - Quebec Community Groups Network (QCGN) (2013)
Keywords: Official Language Minority Community (OLMC)

ACCORD Sample Contract - English Language Arts Network (ELAN) (2012)

Basic Budgeting for an Event - English Language Arts Network (ELAN) (2012)

Publicity Tools - Rooney, Brenda (2012)

Scheduling an Event - Rooney, Brenda (2012)

Book of Proceedings : State of the Arts Summit 2011 - English Language Arts Network (ELAN) (2011)

Marking Milestones - English Language Arts Network (ELAN) (2011)

Imagining a Broadcast and Media Strategy for Quebec's Official Language Minority - English Language Arts Network (ELAN) (2011)
This study revealed several opportunities to increase the quantity and quality of production, which have previously been overlooked, because of a lack of consistent/persistent consultations with a variety of interlocutors. These include: CRTC, Canada Media Fund, Telefilm and Société de développement des enterprises culturelles (SODEC), as well as television broadcasters, including Vidéotron/VOX, which have a responsibility to support or produce community-based television for its English-language subscribers. This study also revealed that a good deal of radio production with strong local content is being created, which could be more widely distributed via the web. A web-based cyber portal could be created to aggregate existing content and make it available to all English-speaking communities throughout Quebec.

Re: CRTC PN 2010-623 : On Contributions by Broadcasting Distribution Undertakings to Local Expression - Rodgers, Guy (2010)

Association for Canadian Studies (ACS) and Quebec Community Groups Network (QCGN) Launch Canadian Diversity Issue Exploring Deep Diversity of English-speaking Quebec - Quebec Community Groups Network (QCGN) (2010)

ELAN Launches Recognizing Artists : Enfin Visibles! - English Language Arts Network (ELAN) (2010)

ELAN Speech to CRTC for Community TV Channel Hearing PN 2009-661 - Rodgers, Guy (2010)

Review of Key Documents on the English-language Film/TV/Media Production Industry in Quebec for the English-language Arts Network of Quebec - Magnetic North Associates (English-Language Arts Network (ELAN), 2010)
Responding to anecdotal evidence from their members, the Quebec chapters of ACTRA and DGC commissioned a major study of English-language production in Quebec based on CAVCO data (Appendix I). This 2008 report was titled “Going…Going…Gone: The Decline of English-language Production in Quebec 1996-7 to 2006-7”, and it demonstrated several long term trends in domestic production.
Keywords: Official Language Minority Community (OLMC)

Survey of the English-language Film/TV/Media Industry in Quebec for the English-language Arts Network of Quebec with funding from Telefilm Canada - Magnetic North Associates (English-Language Arts Network (ELAN), 2010)
There has been a significant shift in the demographic profile of the English-Quebec production industry since the last similar survey of English-Quebec producers in 2003. Today’s industry is more female, has fewer immigrants, and is much more bilingual. Sixty two per cent say they speak fluent French. This demographic shift may be caused by the departure of members of the industry with poorer French language skills or an increase in language skills.
Keywords: Official Language Minority Community (OLMC)

Re: CRTC 2009-661 : Review of Community Television Policy Framework - Rodgers, Guy (2010)

[Notes for a Speech from ELAN to CRTC at Hearing 2009-418] - Rodgers, Guy (2010)

ELAN Response to Questions Raised by the CRTC at the Community TV Hearing, April 30, 2010 - English Language Arts Network (ELAN) (2010)

What is Bill C-32? - English Language Arts Network (ELAN) (2010)
Bill C-32 is officially known as the Copyright Modernization Act. It was an attempt at a “Balanced Copyright” act introduced in Parliament on June 2, 2010, by the Conservative Party — Honourable Tony Clement, Minister of Industry, and the Honourable James Moore, Minister of Canadian Heritage and Official Languages. It contains changes to Canadian Copyright Law that are hotly contested by artists and authors of cultural media. The Bloc, NDP and Liberal parties are opposed to the act being passed in its current state, and are calling for amendments to be made.
Keywords: Official Language Minority Community (OLMC)